Development of an online educational toolkit for sexual orientation and gender identity minority nursing care - Erin Ziegler; Marian Luctkar-Flude; Benjamin Carroll; Jane Tyerman; Lillian Chumbley; Chris Shortall (Universidade de São Paulo, 2021)
Objective: to develop and implement an online education resources to address a gap in nursing education regarding the concept of cultural humility and its application to healthcare encounters with persons who identify as lesbian, gay, bisexual, transgender, queer, intersex (LGBTQI) or Two-Spirit. Improved understanding of LGBTQI and Two-Spirit community health issues is essential to reducing the healthcare access barriers they currently face. Method: an online educational toolkit was developed that included virtual simulation games and curated resources. The development process included community involvement, a team-building meeting, development of learning outcomes, decision-point maps and scriptwriting for filming. A website and learning management system was designed to present learning objectives, curated resources, and the virtual games. Results: the Sexual Orientation and Gender Identity Nursing Toolkit was created to advance cultural humility in nursing practice. The learning toolkit focuses on encounters using cultural humility to meet the unique needs of LGBTQI and Two-Spirit communities. Conclusion: our innovative online educational toolkit can be used to provide professional development of nurses and other healthcare practitioners to care for LGBTQI and Two-Spirit individuals.